CURRENT PRACTICE OF ESSENTIAL CARE FOR MOTHERS AND NEWBORNS DURING AND IMMEDIATELY AFTER CESAREAN SECTION AND ASSOCIATED FACTORS AT DUC GIANG GENERAL HOSPITAL, 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: (1) To describe the current practice of Early Essential Care for Mothers and Newborns (EECMN) during and immediately after cesarean section and (2) to analyse factors associated with its implementation at Duc Giang General Hospital in 2025.Methods: A cross-sectional study with an explanatory sequential mixed-methods design (quantitative followed by qualitative). The quantitative component observed 177 term cesarean sections (≥37 weeks) from April to August 2025 using a 20-item checklist based on Decision No. 6734/QD-BYT (2016); the unit of observation was each operation (care team). The qualitative component comprised in-depth interviews with midwives/nurses, surgical team members and postpartum women to explain influencing factors. Quantitative data were entered in Epidata 3.1 and analysed in SPSS 20.0 (descriptive statistics); qualitative data were thematically analysed.Results: The proportion of cases reaching the pre-defined scoring threshold (≥36/40 points) was 96.0% (170/177). High adherence was observed for oxytocin administration (100%), cord inspection before clamping (98.9%) and correct skin-to-skin placement (96.0%). For skin-to-skin duration, 160/177 (90.4%) sustained the recommended ≥90-minute target, 12/177 (6.8%) had skin-to-skin but for a shorter time, and 5/177 (2.8%) did not receive it; 170/177 (96.0%) completed the first breastfeed within the first hour. The lowest-adherence steps were correct drying sequence (159/177; 89.8%) and checking the resuscitation bag/mask/suction (164/177; 92.7%). Qualitative findings identified staffing shortages, limited post-operative space and privacy, subjective attitudes towards some steps, and maternal barriers (fatigue, nausea, post-spinal hypotension) as the main influencing factors.Conclusions: At the time of the survey, most EECMN steps during cesarean section were performed with high threshold-attainment among eligible observed cases; however, gaps remained in resuscitation-equipment preparation, correct drying sequence and sustaining skin-to-skin for the recommended duration. Periodic supervision, competency-based training and additional staffing are needed. As a cross-sectional study without a comparison group or baseline, the results do not reflect change over time.
Keywords: Early Essential Care for Mothers and Newborns; cesarean section; nurses; midwives; skin-to-skin contact; early initiation of breastfeeding.